GIRAFFA (GIRAFFIDAE, MAMMALIA) FROM THE LOWER SIWALIKS OF PAKISTAN - K. Aftab; M. A. Khan; M. A. Babar; Z. Ahmad; M. Akhtar (Journal of Animal and Plant Sciences, 2016)
Newremains of Giraffa priscilla are recorded from the Middle Miocene localities of Pakistan. The material originates from Chinji Rest House, Rakh Wasnal, Dhok Bun Amir Khatoon, Dhulian, Ghungrilla, Dial, Lava, Phadial, Bhelomar and Ratial. These localities are also well known for the rich Middle Miocene mammalian fauna of the Siwaliks. The estimated age of these localities is 14.2–11.2 Ma, belonging to the Chinji Formation of the Lower Siwaliks. The findings contribute to our understanding of the presence of this species in the Middle Miocene of Pakistan.
Keywords: Mammalia; Vertebrates; Giraffa priscilla; Miocene; Siwaliks